Encoding of High Frequencies Improves with Maturation of Action Potential Generation in Cultured Neocortical Neurons - Nikitin, Evgeny S.; Bal, Natalia V.; Malyshev, Aleksey; Ierusalimsky, Victor N.; Spivak, Yulia; Balaban, Pavel M.; Volgushev, Maxim (Frontiers in Cellular Neuroscience, 2017)
The ability of neocortical neurons to detect and encode rapid changes at their inputs is crucial for basic neuronal computations, such as coincidence detection, precise synchronization of activity and spike-timing dependent plasticity. Indeed, populations of cortical neurons can respond to subtle changes of the input very fast, on a millisecond time scale. Theoretical studies and model simulations linked the encoding abilities of neuronal populations to the fast onset dynamics of action potentials. Experimental results support this idea, however mechanisms of fast onset of action potentials in cortical neurons remain elusive. Studies in neuronal cultures, that are allowing for accurate control over conditions of growth and microenvironment during the development of neurons and provide better access to the spike initiation zone, may help to shed light on mechanisms of action potential generation and encoding. Here we characterize properties of action potential encoding in neocortical neurons grown for 11-25 days in culture. We show that encoding of high frequencies improves upon culture maturation, which is accompanied by the development of passive electrophysiological properties and action potential generation. The onset of action potentials becomes faster with culture maturation. Statistical analysis using correlations and linear model approaches identified the onset dynamics of action potentials as a major predictor of age-dependent changes of encoding. Encoding of high frequencies strongly correlated also with the input resistance of neurons. Finally, we show that maturation of encoding properties of neurons in cultures is similar to the maturation of encoding in neurons studied in slices. These results show that maturation of action potential generators and encoding is, to a large extent, determined genetically and takes place even without normal micro-environment and activity of the whole brain in vivo. This establishes neuronal cultures as a valid experimental model for studying mechanisms of action potential generation and encoding, and their maturation.